Preparation and characterization of jute cellulose nanocrystals using tetrabutylammonium fluoride and dimethyl sulfoxide solutions - Shamsuzzaman Sheikh; Kazumasa Hirogaki; Satoshi Irie; Koji Nakane (SPE Polymers)
Abstract This study reports the efficient extraction of cellulose nanocrystals (CNCs) and preparation of self‐reinforced CNC films from scoured and bleached jute fibers using a unique solvent system combining tetrabutylammonium fluoride and dimethyl sulfoxide and compare the outcomes with commercial nanocellulose. The dissolution time of jute fiber was only 1.5 h at 90°C, which is the shortest time compared to all other methods. Morphological examinations revealed compact agglomeration structures of CNCs under SEM observation. TEM analysis determined an average diameter of 12–45 nm and 8–43 nm for scoured and bleached jute CNCs, respectively. The crystallinity was measured at 79.14% for scoured and 73.59% for bleached jute CNCs. TGA results indicated suitable thermal stability of the produced jute CNCs, demonstrating stability up to 210°C before starting cellulose decomposition. The prepared scoured and bleached jute CNC films exhibited a higher ultimate tensile strength of 18.89 and 42.07 MPa, with elongation at break 27.62% and 56.07%, respectively, making it a suitable solution and eco‐friendly film for packaging applications. Compared to commercial nanocellulose, extracted jute CNCs show identical properties. They are expected to be used as reinforcement with other polymers in nanocomposite films for packaging, coating, pharmaceutical, and biomedical applications. Highlights Jute CNCs and self‐reinforced CNC films are attained using the TBAF/DMSO solvent system. The jute fiber completes rapid dissolution in 1.5 h at 90°C, the shortest time compared to all other methods. The scoured and bleached jute CNCs exhibit average diameters of 12–45 nm and 8–43 nm, with crystallinity of 79.14% and 73.59%, respectively. The fabricated scoured and bleached jute CNC films display ultimate tensile strength of 18.89 and 42.07 MPa and elongation at break 27.62% and 56.07%.